COMPANY Fotografien und Fragmente über das Arbeiten - Schneider, Wolfgang (De Gruyter, 2019)
The artistic research in COMPANY investigates behind the scenes of everyday worklife in a metalworking industrial enterprise.In photographs, videos, and conversations with the workers in this company, the authors search out signs and structures of that "company" with which bread is shared (lat. cum pane), a society which, despite seemingly predetermined rules, is always a work in progress.